The Relationship Of Close Kinetic Chain Exercise To Functional Ability In Osteoarthritis Patients At The Citra Medika Health Center Lubuklinggau City - Utami, Treida; Rusiandy, Rusiandy; Marlena, Feny (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Functional ability refers to a person's capacity to perform tasks related to daily activities, which involves multiple joint and muscle groups to enhance stability. The research addresses the issue of increasing numbers of osteoarthritis patients experiencing functional impairments. The objective of this study is to examine the relationship between close kinetic chain exercise and the functional disability of elderly individuals with osteoarthritis in the Citra Medika Health Center area, Lubuklinggau City.This research employs a quantitative method with a pre-test and post-test design. The treatment group will receive theraband exercise therapy. The study's population consists of 253 individuals, with a sample size of 10 people. The data types include both primary and secondary data. Data analysis is conducted using paired t-test statistics (a parametric test).The findings reveal that the average functional ability score before the close kinetic chain exercise intervention for osteoarthritis patients in the Citra Medika Health Center area, Lubuklinggau City, was 54.50. After the intervention, the average functional ability score improved to 44.70. This indicates a significant relationship between close kinetic chain exercise and functional ability in osteoarthritis patients, with a p-value of 0.000.This research is expected to provide the Citra Medika Health Center in Lubuklinggau City, as well as the relevant professionals, with valuable data and theoretical insights to enhance the quality of nursing care services for osteoarthritis patients by implementing standardized procedures for exercise therapy.carrying out closed kinetic chain exercises in the routine activities of the Community Health Center.